2010
DOI: 10.14742/ajet.1067
|View full text |Cite
|
Sign up to set email alerts
|

Interactive whiteboards: Interactive or just whiteboards?

Abstract: Over the last decade, interactive whiteboards have become popular teaching and learning tools, especially in primary school classrooms. Research studies from recent literature report on high levels of student motivation, teacher enthusiasm and wholeschool support associated with these technological tools. Much research to date has reported on the potential of interactive whiteboards (IWBs) to improve the quality of teaching and learning processes by enhancing levels of interaction, communication and collaborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 17 publications
0
43
0
2
Order By: Relevance
“…This focus was also adopted by other researchers investigating perspectives of successful technology integration (e.g., Northcote, Mildenhall, Marshall, & Swan, 2010;Trinidad, Newhouse, & Clarkson, 2004). These studies included descriptors about teacher capacities such as pedagogical knowledge of technology integrated planning, delivery of student-centred authentic learning experiences incorporating problem solving and higher order thinking skills, and knowledge about social and ethical issues.…”
Section: Background Integrated Technology Use: Focus On Teachers' Clamentioning
confidence: 99%
“…This focus was also adopted by other researchers investigating perspectives of successful technology integration (e.g., Northcote, Mildenhall, Marshall, & Swan, 2010;Trinidad, Newhouse, & Clarkson, 2004). These studies included descriptors about teacher capacities such as pedagogical knowledge of technology integrated planning, delivery of student-centred authentic learning experiences incorporating problem solving and higher order thinking skills, and knowledge about social and ethical issues.…”
Section: Background Integrated Technology Use: Focus On Teachers' Clamentioning
confidence: 99%
“…It is also easier for teachers to design activities facilitating interaction and cooperation between students. Teachers and students feel closer to each other, as Wood (2002) argued, and students are more motivated to concentrate on and participate in teaching activities (Homles, 2009;Northcote et al, 2010;Slay et al, 2008;Smith et al, 2005;Wall et al, 2005). These advantages largely overcome the limitations of PPT slides in teaching and student learning effectiveness.…”
Section: Educational Implicationsmentioning
confidence: 99%
“…The major advantages of IWB indicated in the literature and their potential in Biology teaching are explained as follows (BECTA, 2007;Glover et al, 2005;Holmes, 2009;Northcote et al, 2010;Slay et al, 2008;Smith et al, 2005;Wall et al, 2005) :…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, how experienced and novice teachers differ in their integrative skills in using IWBs is still unclear in current research. More research to explore what specific pedagogical strategies teachers employ during their use of IWBs in different academic domains is also needed since researchers have found that although the IWB is unique in its functions to improve teaching effectiveness, teachers can use it as a general whiteboard (Northcote, Mildenhall, Marshall & Swan, 2010).…”
Section: Implications and Future Researchmentioning
confidence: 99%